2018
DOI: 10.1590/1982-0224-20170119
|View full text |Cite
|
Sign up to set email alerts
|

Management proposal based on the timing of oral incubation of eggs and juveniles in the sentinel species Genidens genidens (Siluriformes: Ariidae) in a tropical estuary

Abstract: Ariids such as Genidens genidens are particularly susceptible to overfishing because of their complex reproductive mechanisms, which result in slow replenishment of stocks. In this study, we obtained data about the reproductive ecology of the catfish G. genidens in the Guanabara Bay estuary, Rio de Janeiro, Brazil, providing supporting information for management of its fishery. The sex ratio, mean size of each sex at first sexual maturation, and female fecundity were determined and the reproductive period was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…This family includes catfish from tropical and subtropical regions, occurring in marine, estuarine and freshwater environments, usually abundant in muddy and shallow bottom coastal waters (Schmidt et al, 2008;Silva-Junior et al, 2013). With catches that have exceeded 28,781 t in Brazil (Freire et al, 2015), they are among the most economically important resources for artisanal fishing, mainly off southeastern and south Brazil (Fischer et al, 2011;Gomes and Araújo, 2004;Maciel et al, 2018a). Ariids can exhibit seasonal movements between environments with different salinities related to different biological aspects, such as reproduction, feeding and ontogeny (Avigliano et al, 2017c;Schmidt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This family includes catfish from tropical and subtropical regions, occurring in marine, estuarine and freshwater environments, usually abundant in muddy and shallow bottom coastal waters (Schmidt et al, 2008;Silva-Junior et al, 2013). With catches that have exceeded 28,781 t in Brazil (Freire et al, 2015), they are among the most economically important resources for artisanal fishing, mainly off southeastern and south Brazil (Fischer et al, 2011;Gomes and Araújo, 2004;Maciel et al, 2018a). Ariids can exhibit seasonal movements between environments with different salinities related to different biological aspects, such as reproduction, feeding and ontogeny (Avigliano et al, 2017c;Schmidt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Genidens genidens (Cuvier, 1829) is one of the most abundant species in estuarine systems off Brazilian coast (Andrade-Tubino et al, 2008;Schmidt et al, 2008), occurring on the eastern coast of South America, from Bahia (Brazil) to Buenos Aires (Argentina), inhabiting shallow coastal waters, estuaries and lagoons (Fischer et al, 2011). This catfish has a peculiar reproductive biology, where females produce large oocytes and males carry out oral incubation of the offspring, with the reproductive period occurring once a year during the hot months, from late spring to early autumn (Maciel et al, 2018a;Wallace and Selman, 1981). Although G. genidens is an important commercial species for artisanal fishery (Silva-Junior et al, 2013), its population structure and life history are not well known, and the few existing management policies aimed at this resource are restricted only to a few regions (MMA, 2004;SUDEPE, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the L 100 value for G. genidens males was calculated at 28.2 cm (Maciel et al, 2018a), the SCP seems to be related to the size in which all males in a given population become mature. For females, although Maciel et al (2018a) calculated that all females of a given population were already adults at 19.3 cm (L 100 ), the same study shows they skip spawning and only begin to spawn at 20 cm, and from 28 cm a considerable increase in fecundity is detected, suggesting that these females reabsorb produced oocytes and skip the reproductive period in order to invest energy in growth, beginning actual reproductive activities when they reach larger body sizes and are more fecund. Folkvord et al (2014) demonstrated that immature fish or those who skipped the spawning season exhibited more pronounced growth rates than individuals carrying out reproduction activities.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, SCP size in females seems to be related to a reproductive strategy aiming at increased fertility, rather than sexual maturation. Since fecundity is related to size increases in this species (Maciel et al, 2018a), the changes in growth pattern occur when individuals are at the peak of their reproductive activity.…”
Section: Discussionmentioning
confidence: 99%